2015
DOI: 10.4238/2015.october.26.19
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL2/IL21 and SH2B3 polymorphisms and risk of celiac disease: a meta-analysis

Abstract: ABSTRACT. Celiac disease (CD) is a common autoimmune disorder characterized by heightened immunological response to ingested gluten. Certain gene polymorphisms of IL2/IL21 (rs6822844 and rs6840978) and SH2B3 (rs3184504) may influence susceptibility to CD, although the effects remain unclear. We performed a meta-analysis of the associations between rs6822844, rs6840978, and rs3184504 polymorphisms and CD risk. PubMed, EMBASE, and the China National Knowledge Infrastructure were searched. ORs and 95%CIs of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Therefore, the Tregs leave the Teff cells without a vital cytokine and disrupt their proliferation, causing metabolic interruption and cell death in these types of cells [29] . Genetic studies on autoimmune diseases have displayed that there is a region on chromosome 4q27 that contribute to IL-2 induction and has confirmed associations with CD [50] . The result of a meta-analysis study by Guo et al [50] on 12,986 CD patients and 28,733 healthy individuals showed that the allele T (rs6822844 and rs6840978) in IL2/IL21 significantly decreased the risk of CD.…”
Section: Suppression By Metabolic Disruptionmentioning
confidence: 93%
“…Therefore, the Tregs leave the Teff cells without a vital cytokine and disrupt their proliferation, causing metabolic interruption and cell death in these types of cells [29] . Genetic studies on autoimmune diseases have displayed that there is a region on chromosome 4q27 that contribute to IL-2 induction and has confirmed associations with CD [50] . The result of a meta-analysis study by Guo et al [50] on 12,986 CD patients and 28,733 healthy individuals showed that the allele T (rs6822844 and rs6840978) in IL2/IL21 significantly decreased the risk of CD.…”
Section: Suppression By Metabolic Disruptionmentioning
confidence: 93%
“…Nevertheless, additional genetic variations are reported as risk factors in CD, which means HLA-DQ2 and HLA-DQ8 do not account for all the genetic susceptibility to CD [106]. For example, two cytokines implicated in CD pathogenesis are encoded by specific gene polymorphisms of IL-2/IL-21 [107]. In the past, non-HLA genetic risk factors were reported [108].…”
Section: Celiac Diseasementioning
confidence: 99%
“…61 Due to the presence of conserved SH2 domain, these variant molecules of SH2B3 can inhibit formation and interaction of the NOD2 intracellular receptor and modulate ERK1/2 and p38MAPK pathways. 62 Importance of the rs3184504 polymorphism within SH2B3 is highlighted as carriers of the minor allele (T) at this locus are more prone to both CD 28,35 and T1D. 10,24,36,37 T Cell Activation Rho GTPase Activating Protein A single polymorphism (rs1738074), a variation mapped within the 5 -UTR region of the T cell activation Rho GTPase activating protein (TAGAP)gene, was noted to confer a protection against T1D.…”
Section: Sh2b Adaptor Proteinmentioning
confidence: 99%